IMPLEMENTASI EKONOMI SYARIAH PADA LUMBUNG PANGAN MASYARAKAT DESA PASIRMALATI - Saddam Hussen; Muhammad Qoes Atieq (JESKaPe: Jurnal Ekonomi Syariah, Akuntansi dan Perbankan, 2021)
The community food barn is an institution located in the village and has an important role namely maintaining food reserves. This institution needs to be considered by all parties because this institution handles the needs of many people. The number of community food barn is decreasing and the quality is still traditional. one thing to note is the economic sistem used by the community food barn. Islamic economics is an economy that pays attention to the interests of the world and the hereafter. In addition, the trend of Islamic economics from year to year is increasing. So that there is a need for research on why The community food barn does not run a sharia economic sistem. This study aims to determine the cause of The community food barn not implementing an Islamic economic sistem, then give the best solution. This study uses a descriptive qualitative method with the type of survey research. data collection techniques using interview and documentation techniques. In this study concludes that ignorance is the cause of not implementing Islamic economics then the solution is to introduce the basics of sharia economics related to contracts that can be used in agriculture.